Weed Management in Sorghum: SS-AGR-06/WG002, rev. 01/2022 - Ferrell, Jason; MacDonald, Gregory; Brecke, Barry; Devkota, Pratap (EDIS, 2022)
This publication provides information on weed control options in sorghum. Written by J. A. Ferrell, G. E. MacDonald, B. J. Brecke, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised January 2022.